PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, PELAKSANAAN SELF-ASSESSMENT, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU E-COMMERCE (Studi Kasus Wajib Pajak Orang Pribadi Pelaku UMKM di Kota Semarang) - Shela Nur Fajriya; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the influence of tax knowledge, taxpayer awareness, application of a self-assessment system, and tax sanctions on taxpayer compliance in micro, small, and medium enterprises (MSMEs) in Semarang City who register their businesses on the e-commerce platform. In this study, there are four independent variables and one dependent variable. The independent variables used consist of tax knowledge, taxpayer awareness, application of the self-assessment system, and tax sanctions, while the dependent variable is taxpayer compliance. The sampling technique used was convenience sampling through the online questionnaire method, with the number of samples determined by the Cochran formula, amounting to 101 respondents. The research data was processed using multiple linear analyses with the IBM SPSS 26.0 program. The study's results found a significant positive influence between tax knowledge, taxpayer awareness, application of the self-assessment system, and tax sanctions on taxpayer compliance behavior.